Conversion of water hyacinth to value-added fuel via hydrothermal carbonization. (15th April 2020) - Zhang, Chaoyue; Ma, Xiaoqian; Chen, Xinfei; Tian, Yunlong; Zhou, Yi; Lu, Xiaoluan; Huang, Tao
Abstract: Hydrothermal carbonization (HTC) of water hyacinth (WH) was investigated to elucidate the effects of reaction temperature, residence time and pH (acid and alkali catalysts) on the chemical properties, combustion behavior and emission properties of hydrochar. Results found that high reaction temperature, long residence time and catalysts were beneficial to ameliorate the fuel properties of hydrochar in terms of calorific value and energy densification, albeit the yield and energetic recovery efficiency got deteriorated. The lower H/C, O/C and N/C ratios of hydrochar reflected more severe dehydration, decarboxylation and denitrogenation reactions within HTC process. SEM images represented that HTC could lead to the fragmentized structure of hydrochar. As HTC progressed, the vibration of hydroxyl and carboxyl groups in hydrochar weakened, which was conductive to improving the hydrophobicity of hydrochar. The combustion characteristics of hydrochar got remarkable upgraded after HTC, whose combustibility index S and combustion stability index Rw were both superior to that of WH. The hydrochar obtained from the addition of alkali catalyst (NaOH) possessed lower emission concentration of SO2 and NOX during combustion, thus demonstrating better emission properties. Overall, HTC was a feasible way to bridge the gap from WH to alternative renewable fuel. Graphical abstract: Image 1 Highlights: Hydrothermal carbonization of water hyacinth was studied. The increased reaction temperature, prolonged residence time and catalysts could promote HTC intensity. The HHV and energy densification of hydrochar followed an uptrend as HTC progressed. The condition of 180-60-7 achieved the optimum combustion performance. The alkali catalyst could reduce the emission of typical pollutants within combustion of hydrochar.